Persepsi dan Intensi PelakuUsaha Mikro Kecil Menengah (UMKM) Terhadap Penggunaan QRIS Sebagai Sistem Pembayaran Digital Pasca Pandemi Covid-19 di Kota Mojokerto - Qonita Rizka Baidowi; Dwiyani Sudaryanti; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research aims to explore factors based on the perceptions and intensity of SMEs on the use of QRIS as a digital payment system after the COVID-19 pandemic in Mojokerto City. This research also uses a qualitative descriptive method that takes material from the field in the form of sentences or pictures, not in the form of numbers or numbers. The sources obtained are from the results of observations, interviews, and documentation. The sample in this research are 3 SMEs and 3 consumers in Mojokerto City and who have used QRIS as payment. There are three indicators used to see the perceptions of SMEs and consumers, namely perceived benefits, perceived ease of use, and perceived risks. There are 2 intensity indicators, namely desire and inhibition. This research shows that MSME actors and consumers have a positive perception of the use of QRIS so that they can form a strong intention to implement QRIS as a digital payment system in the post-COVID-19 pandemic era to date.Keywords: SMEs, QRIS, perception, intention